Large thermoelectric power factors by opening the band gap in semimetallic Heusler alloys. (October 2022) - Garmroudi, Fabian; Parzer, Michael; Riss, Alexander; Beyer, Simon; Khmelevskyi, Sergii; Mori, Takao; Reticcioli, Michele; Bauer, Ernst
Abstract: Efficient thermoelectric devices are typically built from semiconducting materials since their band gap leads to an asymmetry in the continuum of energy-dependent charge transport necessary for a large Seebeck effect. Due to their low cost and excellent mechanical properties half- and full-Heusler compounds have emerged as promising candidates for various applications. Here, we demonstrate how the thermopower of semimetallic Fe2 VAl-based Heusler alloys can be significantly increased by transferring electronic states from within the pseudogap to higher energies. Density functional theory calculations predict that partial Ti and Si co-substitution in Fe2 V1− x Ti x Al1− y Si y drives an opening of the pseudogap, that can be likewise achieved in Fe2 V1− x Ta x Al1− y Si y . Consequently, our experimental measurements on these co-substituted systems reveal exceptionally large thermoelectric power factors (7.3 − 10.3 mWm −1 K −2 near room temperature), as well as average power factors up to 4.6 mWm −1 K −2 in the most pratical temperature range (293 − 573 K). With this work we set the course for a general and reliable way of boosting the thermoelectric performance of semimetallic Heusler alloys. Graphical abstract: Image 1 Highlights: Semimetal-semiconductor transition in full-Heusler compounds. Band gap can be reliably tuned by doping. Seebeck coefficient is significantly enhanced. Huge thermoelectric power factors near room temperature.